Application of crude xylanase from Bacillus licheniformis 77-2 to the bleaching of eucalyptus Kraft pulp - Damiano, V. B.; Bocchini, D. A.; Gomes, E.; Da Silva, R. (Kluwer Academic Publ, 2003)
Alkalophilic Bacillus licheniformis 77-2 produced an extracellular alkali-tolerant xylanase with negligible cellulase activity in medium containing corn straw. The effectiveness of crude xylanase on treatment of eucalyptus Kraft pulp was evaluated. A biobleaching experiment was carried out to compare the chlorine saving with pulp treated and untreated by the enzyme. Two-stage bleaching was employed, using a ClO2 chlorination and NaOH extraction (DE sequence). With the enzymatic treatment, in order to obtain the same value of Kappa number and brightness, respectively 28.5 and 30% less ClO2 was required in comparison to the enzymatically untreated samples.
Keywords: Bacillus licheniformis; biobleaching; Kraft pulp; xylanase